Patient-Specific Assays Based on Whole-Genome Sequencing Data to Measure Residual Disease in Children With Acute Lymphoblastic Leukemia: A Proof of Concept Study - Arthur, Cecilia; Rezayee, Fatemah; Mogensen, Nina; Saft, Leonie; Rosenquist, Richard; Nordenskjöld, Magnus; Harila-Saari, Arja; Tham, Emma; Barbany, Gisela (Frontiers in Oncology, 2022)
Risk-adapted treatment in acute lymphoblastic leukemia (ALL) relies on genetic information and measurable residual disease (MRD) monitoring. In this proof-of-concept study, DNA from diagnostic bone marrow from six children with ALL, without stratifying genetics or central nervous system involvement, underwent whole-genome sequencing (WGS) to identify structural variants (SVs) in the leukemic blasts. Unique sequences generated by SVs were targeted with patient-specific droplet digital polymerase chain reaction (ddPCR) assays. Genomic DNA (gDNA) from bone marrow and cell-free DNA (cfDNA) from plasma and cerebrospinal fluid were analyzed longitudinally. WGS with 30X coverage enabled target identification in all cases. LoQ/LoD for the ddPCR assays (n=15) were up to 10-5 and 10-6, respectively. All targets were readily detectable in a multiplexed ddPCR with minimal DNA input (1 ng of gDNA) at a 10-1 dilution, and targets for half of the patients were also detectable at a 10-2 dilution. The level of MRD in bone marrow at end of induction and end of consolidation block 1 was in a comparable range between ddPCR and clinical routine methods for samples with detectable residual disease, although our approach consistently detected higher MRD values for patients with BCP-ALL. Additionally, several samples with undetectable MRD by flow cytometry were MRD-positive by ddPCR. In plasma, the level of leukemic targets decreased in cfDNA over time following the MRD level detected in BM. cfDNA was successfully extracted from all diagnostic CSF samples (n=6) and leukemic targets were detected in half of these. The results suggest that our approach to design molecular assays, together with ddPCR quantification, is a technically feasible option for accurate MRD quantification and that cfDNA may contribute valuable information regarding MRD and low-grade CNS involvement.